2023
DOI: 10.1038/s41598-023-39728-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sexual function of people with colorectal cancer with and without colostomy bag in Iran: a comparative cross-sectional study

Abstract: The aim of this study was to investigate and compare sexual function in individuals with colorectal cancer, with and without a colostomy bag. A quantitative, descriptive-comparative design was employed, and a cluster random sampling method was used to recruit 252 patients with colorectal cancer. Data collection tools included a participants characteristics form, the International Index of Erectile Function (IIEF) for men, and the Female Sexual Function Index (FSFI) for women. The mean IIEF total score for men … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The effect of various factors such as age, gender, comorbidities, location of the tumor, whether the level of pelvic reflection was lowered during surgery, and the surgical technique applied to the patients (AR, LAR, open surgery, laparoscopic surgery, etc) on ED have been the subject of research in various studies. [12,13] The results of our study showed that age and CCI values significantly differed in the IIEF scores of the patients in the postoperative period (P < .001). A review of the literature suggests that patient age and comorbidities increase the risk of ED in the postoperative period.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The effect of various factors such as age, gender, comorbidities, location of the tumor, whether the level of pelvic reflection was lowered during surgery, and the surgical technique applied to the patients (AR, LAR, open surgery, laparoscopic surgery, etc) on ED have been the subject of research in various studies. [12,13] The results of our study showed that age and CCI values significantly differed in the IIEF scores of the patients in the postoperative period (P < .001). A review of the literature suggests that patient age and comorbidities increase the risk of ED in the postoperative period.…”
Section: Discussionmentioning
confidence: 65%
“…The effect of various factors such as age, gender, comorbidities, location of the tumor, whether the level of pelvic reflection was lowered during surgery, and the surgical technique applied to the patients (AR, LAR, open surgery, laparoscopic surgery, etc) on ED have been the subject of research in various studies. [12,13]…”
Section: Discussionmentioning
confidence: 99%
“…These confounding factors may mask the precise impact of a stoma on sexual functioning. Therefore, it is imperative for future research to specifically address this issue in the context of colon cancer 59 61 .…”
Section: Discussionmentioning
confidence: 99%